Retrieving intracycle interference in angle-resolved laser-assisted photoemission from argon - Hummert, Johan (2020)
We report on a combined experimental and theoretical study of XUV ionization of atomic argon in the presence of a near-infrared (NIR) laser field. Using a table-top source of wavelength-selected femtosecond XUV pulses in combination with a velocity map imaging spectrometer we record angle- and energy-resolved photoelectron distributions and simulate the experimental data by solving the time-dependent Schrödinger equation ab initio. In order to compare with the experimental data we average the calculated energy-angle probability distributions over the experimental focal volume for different values of the magnetic quantum number of the photoelectron. This averaging procedure washes out the intracycle interference pattern, which would otherwise be observed in the form of angular modulations of the photoelectron spectra. We recover these modulations experimentally and in the simulations by evaluating the difference between two averaged distributions that are obtained for slightly different NIR laser field intensities.